Minors or suspects? A discussion of the legal and ethical issues surrounding the indefinite storage of DNA collected from children aged 10–18 years on the National DNA Database in England and Wales - Mansel, Charlotte; Davies, Sharon (Medicine, science, and the law, 2012)
There are currently over 250,000 children between the ages of 10 and 18 years who have their genetic information stored on the National DNA Database. This paper explores the legal and ethical issues surrounding this controversial subject, with particular focus on juvenile capacity and the potential results of criminalizing young children and adolescents. The implications of the adverse legal judgement of the European Court of Human Rights in S and Marper v UK (2008) and the violation of Article 8 of the Convention are discussed. The authors have considered the requirement to balance the rights of the individual, particularly those of minors, against the need to protect the public and have compared the position in Scotland to that of the rest of the UK. The authors conclude that a more ethically acceptable alternative could be the creation of a separate forensic database for children aged 10–18 years, set up to safeguard the interests of those who have not been convicted of any crime.